Analisis Kesalahan Siswa dalam Mengerjakan Soal pada Penjumlahan dan Pengurangan Bilangan Bulat Berbasis HOTS pada Siswa Kelas V - Anggarani, Ninik; Rosidah Aliim Hidayat (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to 1) Describe the errors made by students in solving addition and subtraction problems based on HOTS integers, 2) Describe the causes of errors made by students in working on addition and subtraction problems based on HOTS integers.This research is a descriptivequantitative research. Data collection techniques in this study were written test techniques, observation, interviews, and dosumentation. The research instrument consisted of a test sheet, an observation guide, and an interview guide. Test the validity ofthe data used in this study using triangulation. The data analysis technique used Milles and Huberman model analysis ehich consisted of data presentation, and drawing conclusions.The results of this study indicate that the errors made by students are (1)errors in the final answer (31,22%); (2) errors in undestanding the core (32,18%); (3) errors in the completion step (20,45%); (4) errors in reading the questions (0%). This is because students do not understand the concept, so students are not able to findsolutions in solving problems in the problem. So thet students do not find the results correctly and cause students to make mistakes in working on the questions.